THU0527 Lesinurad, A Selective Uric Acid Reabsorption Inhibitor, in Combination with Xanthane Oxidase Inhibitors: SUA and Flares Composite Endpoint from Phase III Studies in Gout Patients (Clear 1, Clear 2 and Crystal). (15th July 2016) - Khanna, P.P.; Baumgartner, S.; Robinson, J.; Tafesse, E.; Morlock, R.
Abstract : Background: Lesinurad (RDEA594) is a selective uric acid reabsorption inhibitor (SURI) investigated for treatment of gout in combination with xanthine oxidase inhibitors (XOI). Objectives: Investigate efficacy as assessed by a composite endpoint of serum uric acid (sUA) target and no flares in gout patients with inadequate response to XOIs alone from three Phase 3 clinical trials examining treatment with lesinurad in combination with allopurinol (ALLO) or febuxostat (FBX). Methods: CLEAR 1 (NCT01510158 ), CLEAR 2 (NCT01493531 ) and CRYSTAL (NCT01510769 ) were 12-month, randomized, double-blind, Phase III trials to evaluate lesinurad (LESU; 200 mg or 400 mg oral, qd) in combination with ALLO vs ALLO + placebo (PBO) (CLEAR 1 and 2) or in combination with FBX vs FBX+PBO (CRYSTAL). A post-hoc composite endpoint defined as the proportion of patients reaching target sUA level (<6 mg/dL in CLEAR 1 and CLEAR 2 and <5 mg/dL in CRYSTAL) and no gout flares was assessed monthly starting at month 7 (after flare prophylaxis was to be discontinued) in each study and in a pooled analysis. Results: CLEAR 1 (N=603), CLEAR 2 (N=610), and CRYSTAL (N=324) patients, respectively, were primarily male (94.0%, 96.2%, and 95.4%); mean ± SD age was 51.9 ± 11.3, 51.2 ± 10.9, and 54.1 ± 11.0 years and duration since gout diagnosis was 11.8 ± 9.4, 11.5 ± 9.3, and 14.7 ± 10.9 years. Most CLEAR 1 and CLEAR 2 patients (90.5% and 84.1%) received ALLO 300 mg daily (range: 200–600 mg and 200–900 mg, respectively). For CLEAR 1 and CLEAR 2, LESU at both doses in combination with ALLO significantly increased proportions of patients achieving the composite endpoint (sUA target <6.0 mg/dL and no flares) vs ALLO+PBO at all visits, with approximately twice as many LESU patients achieving the composite endpoint (p<0.001). For CRYSTAL, LESU at both doses in combination with FBX increased proportions of patients achieving the composite endpoint (sUA target <5.0 mg/dL and no flares) vs FBX+PBO at all visits, with approximately 40% more LESU patients achieving the composite endpoint (p=0.374 to p=0.002). A pooled analysis of LESU at both doses in combination with ALLO or FBX significantly increased proportions of patients achieving the composite endpoint sUA target vs ALLO+PBO or FBX+PBO at all visits, with approximately twice as many LESU patients achieving the composite endpoint (p<0.001). Sensitivity analysis comparing gout flares requiring treatment (rather than all flares) and sustained achievement of composite endpoint were also carried out. Conclusions: Significantly greater proportions of patients responded to the combination of lesinurad (200 or 400 mg) + XOI, with approximately twice as many achieving the composite endpoint of sUA target and no flares compared with patients treated with XOI+PBO. Combination therapy with lesinurad + XOI represents an option for gout patients who warrant additional therapy Acknowledgement: Research sponsored by Ardea Biosciences/AstraZeneca. Editorial support was provided by PAREXEL and funded by AstraZeneca. Disclosure of Interest: P. Khanna Grant/research support from: AstraZeneca, S. Baumgartner Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group, J. Robinson Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group, E. Tafesse Employee of: AstraZeneca, R. Morlock Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group